Novel Voltage-Mode PID Controller Using a Single CCTA and All Grounded Passive Components - Mongkolwai, Pratya; Tangsrirat, Worapong; Suesut, Taweepol (My University, 2022)
A compact voltage-mode proportional-integral-derivative (PID) controller based on the utilization of a single current conveyor transconductance amplifier (CCTA) is presented in this paper. The presented active PID controller is made up of a single CCTA, and four truly grounded passive components, i.e. two resistors, and two capacitors. The design consideration of the controller parameters has been examined. Besides, the crucial sensitivity performances of the controller parameters for ideal and non-ideal conditions have also been discussed. An application on the closed-loop test system is demonstrated to validate the practicability of the proposed PID controller circuit. To confirm the theoretical behavior, the proposed circuit is simulated with the PSPICE program using TSMC 0.35-μm CMOS process technology. Experimental test results based on commercially available CFOA AD844 and OTA CA3080 integrated circuits are also provided to demonstrate the practicality of the proposed circuit.
Keywords: Current Conveyor Transconductance Amplifier (CCTA); feedback control system; proportional-integral-derivative (PID) controllers; voltage-mode circuit